A preliminary efficacy study of eye movement desensitisation and reprocessing therapy in reducing epilepsy-related anxiety - Broekman-Labinac, K.; Aben, L.; Thijs, R.D.; Smeding, H.M.M.; de Jongh, A.; van der Hiele, K. (Epilepsy & behavior, 2025)
[Display omitted] •EMDR therapy significantly reduced anxiety in people with epilepsy up to three months after therapy.•EMDR therapy for epilepsy-related anxiety improved health-related quality of life up to three months after therapy.•EMDR therapy for epilepsy-related anxiety showed a trend towards improved self-perceived subjective cognitive functioning.•EMDR therapy for epilepsy-related anxiety showed no evidence of affecting seizure frequency.•EMDR therapy is a potentially safe treatment for people with epilepsy. To determine whether eye movement desensitisation and reprocessing (EMDR) therapy reduces anxiety in people with epilepsy-related anxiety. Secondary outcomes included health-related quality of life (HRQOL), subjective cognitive functioning and seizure frequency. Prospective uncontrolled study with a pre-post follow-up design, including measurements before, immediately after, and three months after EMDR therapy, focused on the individuals’ fear of future seizures (i.e. flashforwards). We recruited participants with epilepsy-related anxiety from a Dutch tertiary epilepsy centre. Questionnaires were used to monitor general and epilepsy-related anxiety, HRQOL, subjective cognitive functioning and seizure frequency. Repeated-measures ANOVA was used. Eleven participants were included. We observed a significant reduction in general and epilepsy-related anxiety from before to immediately after EMDR treatment, and three months hereafter (p ≤ 0.001, η2 = 0.698 and p ≤ 0.001, η2 = 0.641, respectively). This coincided with an improvement in HRQOL (p ≤ 0.001, η2 = 0.550). Despite a main treatment effect for subjective cognitive functioning (p = 0.023, η2 = 0.415), no significant post hoc effects were observed. No effects were found for informant-reported cognitive functioning (p = 0.261, η2 = 0.236) and seizure frequency (p = 0.495, η2 = 0.075). This study provides preliminary evidence that EMDR therapy reduces anxiety in people with epilepsy-related anxiety. This effect sustained over three months and coincided with an improved HRQOL. Subjective cognitive functioning and seizure frequency did not change over time. Our findings suggest that EMDR therapy is a potentially safe treatment for epilepsy-related anxiety.